2017
DOI: 10.1126/science.aam8561
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite in Earth’s deep interior

Abstract: Silicate perovskite-type phases are the most abundant constituent inside our planet and are the predominant minerals in Earth's lower mantle more than 660 kilometers below the surface. Magnesium-rich perovskite is a major lower mantle phase and undergoes a phase transition to post-perovskite near the bottom of the mantle. Calcium-rich perovskite is proportionally minor but may host numerous trace elements that record chemical differentiation events. The properties of mantle perovskites are the key to understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 95 publications
3
56
0
Order By: Relevance
“…The inserted high-resolution TEM (HR-TEM) images in Figure 1b,c show the lattice plane of (200) and (211), respectively, for pristine and K + -based CsPb(Br/Cl) 3 NCs, which further indicates that the addition of K + does not influence the crystal structure of NCs. The NCs exhibit a slight increase in size with the incorporation of K + , as shown in the size distribution histograms in Figure 1d,e, where the average sizes of the pristine and K + -based CsPb(Br/Cl) 3 NCs are 9.94 and 10.92 nm, respectively. This result appears inconsistent with our XRD measurement; however, it can be observed that the FWHM of the size distributions also increases with the incorporation of K + .…”
Section: Structure Characterizationmentioning
confidence: 94%
See 3 more Smart Citations
“…The inserted high-resolution TEM (HR-TEM) images in Figure 1b,c show the lattice plane of (200) and (211), respectively, for pristine and K + -based CsPb(Br/Cl) 3 NCs, which further indicates that the addition of K + does not influence the crystal structure of NCs. The NCs exhibit a slight increase in size with the incorporation of K + , as shown in the size distribution histograms in Figure 1d,e, where the average sizes of the pristine and K + -based CsPb(Br/Cl) 3 NCs are 9.94 and 10.92 nm, respectively. This result appears inconsistent with our XRD measurement; however, it can be observed that the FWHM of the size distributions also increases with the incorporation of K + .…”
Section: Structure Characterizationmentioning
confidence: 94%
“…[29][30][31] X-ray diffraction (XRD) and transmission electron microscopy (TEM) measurements are performed to investigate the effects of K + on the structural properties of the resulting NCs. All the samples show evident diffraction peaks around 2θ = 15.00°, 21.00°, 31.00°, 34.00°, 38.00°, and 44.00°, corresponding to the (100), (110), (200), (210), (211), and (220) crystal planes of the cubic CsPb(Br/Cl) 3 phase, respectively (Figure 1a). No diffraction peak shift can be observed in the K + -based samples, suggesting that K + remains outside the perovskite NCs rather than being incorporated into the perovskite lattice.…”
Section: Structure Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Perovskites are materials with stoichiometry ABX 3 that crystallize in the well-known structure named for crystallographer Lev Perovski. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Perovskites are materials with stoichiometry ABX 3 that crystallize in the well-known structure named for crystallographer Lev Perovski.…”
Section: Introductionmentioning
confidence: 99%